PEMBINAAN DAN PENDAMPINGAN KADER POSYANDU BAYI DAN BALITA DALAM PELAYANAN MTBS UNTUK PENCEGAHAN STUNTING DI KELURAHAN LILIBA KOTA KUPANG - Agustina Ina; Jane Leo Mangi; Loriana Lorinda Manalor; Yustinus Rindu; Oklan BT Liunokas; Dominggos Goncalves (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The prevalence of stunting in Indonesia and in East Nusa Tenggara province is still high. Cadres are the spearhead of health services in Indonesia, whose role is very important in helping to alleviate stunting. Management of Sick Toddlers (IMCI) is one way to reduce morbidity rates in infants and toddlers so that stunting can be prevented and reduced. Liliba Village is part of the Oepoi Health Center working area and has the highest incidence of pneumonia compared to other villages. Methods: This community service was carried out using the method of socialization and assistance to cadres carried out at 2 posyandu, namely Melati 11 and 12: This community service is carried out by providing additional food, measuring antopometry and counseling and mentoring cadres for simple handling of sick toddlers. Results: All cadres involved in this activity experienced an increase in knowledge about simple handling of sick toddlers. Two children who were undernourished 100% gained weight and height after 90 days of supplementary feeding and assistancev